A surface modifier and modification process for enhancing the performance of metal catalysts for carbon dioxide electroreduction
Patent Information
- Application Number
- CN202310663810.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-06
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-06-06
AI Technical Summary
现有报道中主要使用了PVDF、PVA、1-十八硫醇等药品对金属催化剂表面进行修饰以提高其疏水性,然而这种表面修饰存在稳定性差的缺点
[0020] Compared with existing technologies, this invention uses a weakly acidic solution of chitin, deacetylated chitin, or cellulose at a certain concentration as a modifier. The raw materials are non-toxic, harmless, inexpensive, and have good stability. Furthermore, this invention provides a modification process for enhancing the carbon dioxide electroreduction performance of metal catalysts. Compared with traditional modification processes, this process is simple to operate, has low processing costs, and the modified metal catalyst exhibits excellent carbon dioxide electrocatalytic performance.
Smart Images

Figure CN116876030B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalytic materials, specifically relating to a surface modifier and modification process for enhancing the carbon dioxide electroreduction performance of metal catalysts. Background Technology
[0002] Currently, with industrial development and progress, carbon dioxide emissions are excessively high, causing a series of climate problems such as global warming. Carbon dioxide electroreduction technology is an important technology that can simultaneously achieve the dual goals of reducing carbon dioxide emissions and producing fuel chemicals. However, traditional metal catalysts exhibit low current density and poor product selectivity during the catalytic process, hindering the practical application of this technology. To address these issues, researchers have proposed various methods to improve catalyst performance, such as altering the catalyst's morphology and structure, changing its crystal orientation, and surface modification. Among these methods, surface modification of metal catalysts offers advantages such as high feasibility, low equipment requirements, and short processing time, making it one of the most promising methods for industrialization.
[0003] Currently, reported methods for surface modification of metal catalysts mainly fall into two categories: altering the hydrophilicity / hydrophobicity of the catalyst surface and modifying the catalyst surface microenvironment. Existing reports primarily utilize reagents such as PVDF, PVA, and 1-octadecyl mercaptan to modify the surface of metal catalysts to improve their hydrophobicity; however, this surface modification suffers from poor stability. Furthermore, existing modifiers that can alter the catalyst surface microenvironment are toxic, harmful, and difficult to prepare.
[0004] This invention proposes a surface modifier and modification process for enhancing the carbon dioxide electroreduction performance of metal catalysts. This process is simple to operate, has low cost, and causes little environmental pollution. Summary of the Invention
[0005] The purpose of this invention is to solve the above-mentioned technical problems existing in the prior art and to provide a surface modifier and modification process for enhancing the carbon dioxide electroreduction performance of metal catalysts.
[0006] To achieve the objective of this invention, the technical solution adopted is as follows:
[0007] Design a surface modifier for enhancing the carbon dioxide electroreduction performance of metal catalysts, wherein the surface modifier is a weakly acidic aqueous solution of chitin, deacetylated chitin, or cellulose.
[0008] Furthermore, the weakly acidic aqueous solution is a 1.5-2.5% aqueous solution of acetic acid.
[0009] Furthermore, the concentration of the weakly acidic aqueous solution of the chitin is 5–10 g / L. The deacetylated chitin is chitosan with a degree of deacetylation of 70%–90%, and its concentration in the weakly acidic aqueous solution is 5–10 g / L.
[0010] Furthermore, the concentration of the weakly acidic aqueous solution of the cellulose is 5–10 g / L.
[0011] This invention also provides a modification process for enhancing the carbon dioxide electroreduction performance of metal catalysts, characterized by comprising the following steps:
[0012] a) Prepare a metal catalyst dispersion;
[0013] b) After adding the surface modifier according to any one of claims 1-5 to the metal catalyst dispersion, let it stand for a certain period of time to allow the surface of the metal catalyst to come into full contact with the modifier;
[0014] c) Separate and clean the metal catalyst processed in step b);
[0015] d) The metal catalyst obtained after treatment in step c) is dried to obtain the modified metal catalyst.
[0016] Further, in step c), the metal catalyst treated in step b) is centrifuged, ultrasonically cleaned with anhydrous ethanol, and then centrifuged again.
[0017] Further, the metal catalyst in step a) is a metal nanoparticle or nanosheet with a diameter of 10-200 nm, and the concentration of the metal catalyst dispersion is 0.8-1.2 mg / mL.
[0018] Furthermore, the metal nanoparticles or nanosheets are one of copper, silver, gold, bismuth, indium, or tin.
[0019] Further, in step b), the mixing volume ratio of the metal dispersion to the surface modifier is (8-12) to 1.
[0020] Compared with existing technologies, this invention uses a weakly acidic solution of chitin, deacetylated chitin, or cellulose at a certain concentration as a modifier. The raw materials are non-toxic, harmless, inexpensive, and have good stability. Furthermore, this invention provides a modification process for enhancing the carbon dioxide electroreduction performance of metal catalysts. Compared with traditional modification processes, this process is simple to operate, has low processing costs, and the modified metal catalyst exhibits excellent carbon dioxide electrocatalytic performance. Attached Figure Description
[0021] The present invention will now be further described with reference to the accompanying drawings.
[0022] Figure 1 This is a TEM image of the copper metal catalyst after surface modification in Example 1.
[0023] Figure 2 The image shows the LSV diagrams of the catalyst before and after modification in Example 1.
[0024] Figure 3 The image shows the Faraday efficiency distribution of hydrogen, single-carbon products, and multi-carbon products of the catalyst modified in Example 1 at different current densities.
[0025] Figure 4 This is a TEM image of the copper metal catalyst after surface modification in Example 3.
[0026] Figure 5 The diagram shows the Faraday efficiency distribution of hydrogen and multi-carbon products of the modified catalyst in Example 3 at different current densities. Detailed Implementation
[0027] The present invention will now be described in further detail with reference to specific embodiments and accompanying drawings.
[0028] Example 1
[0029] 1.5 g of copper sulfate pentahydrate was dissolved in 60 mL of deionized water to prepare a copper sulfate solution. Separately, a sodium borohydride aqueous solution was prepared and added dropwise to the prepared copper sulfate solution until no more bubbles were generated. The resulting solution was centrifuged and dried to obtain a metal powder. 10 mg of the metal powder was weighed and dispersed in 10 mL of deionized water to obtain a uniformly dispersed copper nanoparticle dispersion. The sodium borohydride aqueous solution was prepared by dissolving 0.07 g of sodium borohydride in 40 mL of deionized water.
[0030] Prepare a surface modifier by dissolving 0.8g of chitosan powder with a degree of deacetylation of 70% in 100mL of 2% acetic acid aqueous solution.
[0031] The surface modifier was gradually added to the copper nanoparticle dispersion, with a volume ratio of surface modifier to copper nanoparticle dispersion of 10:1. The mixture was then allowed to stand for 20 minutes to allow the surface modifier to fully contact and coat the surface of the copper nanoparticles.
[0032] The mixture obtained in the above steps was centrifuged at 8500 rpm / rcf for 5 min to obtain surface-modified copper nanoparticle powder. Subsequently, the modified powder obtained by centrifugation was ultrasonically dispersed in anhydrous ethanol and then centrifuged and washed again at the same speed, repeating this process twice. Finally, the centrifuged and washed powder was vacuum dried to obtain the modified metal powder.
[0033] Weigh 10 mg of the modified metal powder and ultrasonically disperse it in 10 ml of a mixed solution of ethanol and water, wherein the ratio of ethanol to water is 1:1. Then, add 10 μL of Nafion solution dropwise to the dispersion to obtain a catalyst slurry. Spray the catalyst slurry onto a surface with an area of 1 cm². -2 The catalyst loading on the hydrophobic carbon paper was 1 mg / cm³. -2 The cathode electrode was obtained. The cathode electrode was then assembled in a flow reaction cell for carbon dioxide electroreduction testing. The test conditions were as follows: an Ag / AgCl electrode was used as the reference electrode, and nickel foam was used as the anode electrode. The electrolyte for both the cathode and anode was 1M KOH, with a flow rate of 20 ml / min; the gas introduced into the cathode was high-purity carbon dioxide, with a flow rate of 20 sccm.
[0034] In the attached diagram Figure 1 TEM images of the surface-modified copper metal catalyst show that the surface of the modified copper metal particles is covered with a modified layer. Figure 2 The LSV diagrams of the catalyst before and after modification show that the modified catalyst has better catalytic activity. Figure 3 The diagram shows the Faraday efficiency distribution of the modified catalyst for hydrogen, single-carbon products, and multi-carbon products at different current densities.
[0035] Example 2
[0036] Prepare a silver nitrate solution by dissolving 0.15 g of silver nitrate in 40 mL of deionized water. Separately, prepare a sodium borohydride aqueous solution and add it dropwise to the prepared silver nitrate solution until no more bubbles are generated. Centrifuge and dry the resulting solution to obtain a metal powder. Weigh 10 mg of the metal powder and disperse it in 10 mL of deionized water to obtain a uniformly dispersed copper nanoparticle dispersion. The sodium borohydride aqueous solution is prepared by dissolving 0.07 g of sodium borohydride in 40 mL of deionized water.
[0037] Prepare a surface modifier by dissolving 0.8g of chitosan powder with a degree of deacetylation of 70% in 100mL of 2% acetic acid aqueous solution.
[0038] The surface modifier was gradually added to the silver nanoparticle dispersion, with a volume ratio of surface modifier to silver nanoparticle dispersion of 10:1. The mixture was then allowed to stand for 20 minutes to allow the surface modifier to fully contact and coat the surface of the silver nanoparticles.
[0039] The mixture obtained in the above steps was centrifuged at 8500 rpm / rcf for 5 min to obtain surface-modified silver nanoparticle powder. Subsequently, the modified powder obtained by centrifugation was ultrasonically dispersed in anhydrous ethanol and then centrifuged and washed again at the same speed, repeating this process twice. Finally, the centrifuged and washed powder was vacuum dried to obtain the modified metal powder.
[0040] Weigh 10 mg of the modified metal powder and ultrasonically disperse it in 10 ml of a mixed solution of ethanol and water, wherein the ratio of ethanol to water is 1:1. Then, add 10 μL of Nafion solution dropwise to the dispersion to obtain a catalyst slurry. Spray the catalyst slurry onto a surface with an area of 1 cm². -2 The catalyst loading on the hydrophobic carbon paper was 1 mg / cm³. -2 The cathode electrode was obtained. The cathode electrode was then assembled in a flow reaction cell for carbon dioxide electroreduction testing. The test conditions were as follows: an Ag / AgCl electrode was used as the reference electrode, and nickel foam was used as the anode electrode. The electrolyte for both the cathode and anode was 1M KOH, with a flow rate of 20 ml / min; the gas introduced into the cathode was high-purity carbon dioxide, with a flow rate of 20 sccm.
[0041] Example 3
[0042] 1.5 g of copper sulfate pentahydrate was dissolved in 60 mL of deionized water to prepare a copper sulfate solution. Separately, a sodium borohydride aqueous solution was prepared and added dropwise to the prepared copper sulfate solution until no more bubbles were generated. The resulting solution was centrifuged and dried to obtain a metal powder. 10 mg of the metal powder was weighed and dispersed in 10 mL of deionized water to obtain a uniformly dispersed copper nanoparticle dispersion. The sodium borohydride aqueous solution was prepared by dissolving 0.07 g of sodium borohydride in 40 mL of deionized water.
[0043] Prepare a surface modifier by dissolving 0.5g of cellulose powder in 100mL of deionized water.
[0044] The surface modifier was gradually added to the copper nanoparticle dispersion, with a volume ratio of surface modifier to copper nanoparticle dispersion of 10:1. The mixture was then allowed to stand for 20 minutes to allow the surface modifier to fully contact and coat the surface of the copper nanoparticles.
[0045] The mixture obtained in the above steps was centrifuged at 8500 rpm / rcf for 5 min to obtain surface-modified copper nanoparticle powder. Subsequently, the modified powder obtained by centrifugation was ultrasonically dispersed in anhydrous ethanol and then centrifuged and washed again at the same speed, repeating this process twice. Finally, the centrifuged and washed powder was vacuum dried to obtain the modified metal powder.
[0046] Example 4
[0047] 0.2 g of bismuth nitrate was dissolved in 40 mL of deionized water to prepare a bismuth nitrate solution. Separately, a sodium borohydride aqueous solution was prepared and added dropwise to the prepared silver nitrate solution until no more bubbles were generated. The resulting solution was centrifuged and dried to obtain a metal powder. 10 mg of the metal powder was weighed and dispersed in 10 mL of deionized water to obtain a uniformly dispersed copper nanoparticle dispersion. The sodium borohydride aqueous solution was prepared by dissolving 0.07 g of sodium borohydride in 40 mL of deionized water.
[0048] Prepare a surface modifier by dissolving 0.8g of chitosan powder with a degree of deacetylation of 90% in 100mL of 2% acetic acid aqueous solution.
[0049] The surface modifier was gradually added to the bismuth nanosheet dispersion, with a volume ratio of surface modifier to bismuth nanosheet dispersion of 10:1. The mixture was then allowed to stand for 20 minutes to allow the surface modifier to fully contact and coat the surface of the silver-bismuth nanosheets.
[0050] The mixture obtained from the above steps was centrifuged at 8500 rpm / rcf for 5 min to obtain surface-modified bismuth nanosheets. Subsequently, the modified powder obtained by centrifugation was ultrasonically dispersed in anhydrous ethanol and then centrifuged and washed again at the same speed, repeated twice. Finally, the centrifuged and washed powder was vacuum dried to obtain the modified metal powder.
[0051] 10 mg of modified bismuth nanosheets were weighed and ultrasonically dispersed in 10 ml of a mixed solution of ethanol and water, wherein the ratio of ethanol to water was 1:1. Then, 10 μL of Nafion solution was added dropwise to the dispersion to obtain a catalyst slurry. The catalyst slurry was sprayed onto a 1 cm² area... -2 The catalyst loading on the hydrophobic carbon paper was 1 mg / cm³. -2 The cathode electrode was obtained. The cathode electrode was then assembled in a flow reaction cell for carbon dioxide electroreduction testing. The test conditions were as follows: an Ag / AgCl electrode was used as the reference electrode, and nickel foam was used as the anode electrode. The electrolyte for both the cathode and anode was 1M KOH, with a flow rate of 20 ml / min; the gas introduced into the cathode was high-purity carbon dioxide, with a flow rate of 20 sccm.
[0052] Comparative example:
[0053] 1.5 g of copper sulfate pentahydrate was dissolved in 60 mL of deionized water to prepare a copper sulfate solution. Separately, a sodium borohydride aqueous solution was prepared and added dropwise to the prepared copper sulfate solution until no more bubbles were generated. After the reaction was complete, a uniformly dispersed copper nanoparticle dispersion was obtained. The sodium borohydride aqueous solution was prepared by dissolving 0.07 g of sodium borohydride in 40 mL of deionized water.
[0054] The copper nanoparticle dispersion obtained in the above steps was centrifuged at 8500 rpm / rcf for 5 min to obtain copper nanoparticle powder. Subsequently, the centrifuged copper nanoparticles were ultrasonically dispersed in anhydrous ethanol and then centrifuged and washed again at the same speed, repeating the process twice. Finally, the centrifuged and washed powder was vacuum dried to obtain copper metal powder.
[0055] The Faraday efficiencies of the carbon dioxide electroreduction products of the above comparative examples and Example 1 are shown in Table 1:
[0056] Table 1. Faraday efficiency of carbon dioxide electroreduction products in Examples 1, 3, and the comparative example.
[0057]
[0058]
[0059] As shown in Table 1, the surface modifier and its modification process described in this invention can significantly improve the carbon dioxide electrocatalytic performance of the catalyst, with a Faradaic efficiency of up to 83.7% for multi-carbon products (ethylene, ethanol, acetic acid), compared to only 28.3% for the unmodified catalyst in the comparative example.
[0060] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "one example," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0061] The above description, in conjunction with specific embodiments, provides a further detailed explanation of the present invention, but it should not be construed as limiting the specific implementation of the invention to these descriptions. For those skilled in the art, several simple deductions or substitutions can be made without departing from the concept of the present invention.
Claims
1. A modification process for enhancing the carbon dioxide electroreduction performance of metal catalysts, characterized in that, It includes the following operating steps: a) Prepare a metal catalyst dispersion, wherein the metal catalyst is metal nanoparticles or nanosheets with a diameter of 10-200 nm, and the concentration of the metal catalyst dispersion is 0.8-1.2 mg / mL; wherein the metal nanoparticles or nanosheets are one of copper, silver, gold, bismuth, indium or tin. b) After adding a surface modifier to the metal catalyst dispersion, the mixture is allowed to stand for a certain period of time to allow the surface of the metal catalyst to come into full contact with the modifier. The surface modifier is a weakly acidic aqueous solution of chitin, deacetylated chitin, or cellulose, and the weakly acidic aqueous solution is an aqueous solution of acetic acid. c) Separate and clean the metal catalyst processed in step b); d) The modified metal catalyst is obtained by drying the metal catalyst obtained in step c).
2. The modification process for enhancing the carbon dioxide electroreduction performance of metal catalysts according to claim 1, characterized in that: In step c), the metal catalyst treated in step b) is centrifuged, ultrasonically cleaned with anhydrous ethanol, and then centrifuged again.
3. The modification process for enhancing the carbon dioxide electroreduction performance of metal catalysts according to claim 1, characterized in that: In step b), the mixing volume ratio of the metal dispersion to the surface modifier is 8-12 to 1.
4. The modification process for enhancing the carbon dioxide electroreduction performance of metal catalysts according to claim 1, characterized in that: The weakly acidic aqueous solution is a 1.5-2.5% aqueous solution of acetic acid.
5. The modification process for enhancing the carbon dioxide electroreduction performance of metal catalysts according to claim 1, characterized in that: The concentration of the weakly acidic aqueous solution of the chitin is 5-10 g / L; the deacetylated chitin is chitosan with a degree of deacetylation of 70%-90%, and its concentration in the weakly acidic aqueous solution is 5-10 g / L.
6. The modification process for enhancing the carbon dioxide electroreduction performance of metal catalysts according to claim 1, characterized in that: The concentration of the weakly acidic aqueous solution of the cellulose is 5–10 g / L.